Genome-Wide Single Nucleotide Polymorphism Typing Method for Identification of Bacillus anthracis Species and Strains among B. cereus Group Species - Kuroda, Makoto (American Society for Microbiology (ASM), 2010)
As an issue of biosecurity, species-specific genetic markers have been well characterized. However, Bacillus anthracis strain-specific information is currently not sufficient for traceability to identify the origin of the strain. By using genome-wide screening using short read mapping, we identified strain-specific single nucleotide polymorphisms (SNPs) among B. anthracis strains including Japanese isolates, and we further developed a simplified 80-tag SNP typing method for the primary investigation of traceability. These 80-tag SNPs were selected from 2,965 SNPs on the chromosome and the pXO1 and pXO2 plasmids from a total of 19 B. anthracis strains, including the available genome sequences of 17 strains in the GenBank database and 2 Japanese isolates that were sequenced in this study. Phylogenetic analysis based on 80-tag SNP typing showed a higher resolution power to discriminate 12 Japanese isolates rather than the 25 loci identified by multiple-locus variable-number tandem-repeat analysis (MLVA). In addition, the 80-tag PCR testing enabled the discrimination of B. anthracis from other B. cereus group species, helping to identify whether a suspected sample originates from the intentional release of a bioterrorism agent or environmental contamination with a virulent agent. In conclusion, 80-tag SNP typing can be a rapid and sufficient test for the primary investigation of strain origin. Subsequent whole-genome sequencing will reveal apparent strain-specific genetic markers for traceability of strains following an anthrax outbreak.